DEVELOPMENT OF BRASSICA NAPUS L. LINES FOR HIGH YIELD AND ESSENTIAL FATTY ACIDS - AWAN, AR; ABBAS, M; HASSAN, A; SARDAR, S; AKBAR, S; NAEEM, A; QADIR, MS; ALI, W; NAWAZ, MS; AQEEL, M; MAHMOOD, N (Biological and Clinical Sciences Research Journal, 2023)
Heterosis and combining ability were calculated for 13 different morphological, yield, and quality-related traits of 18 F1 Brassica napus hybrids developed through line × tester mating design using 6 lines and 3 testers along with their parents. Line × tester ANOVA revealed highly significant results among all characters except for primary branches per plant. ZM-R-2 (tester) was identified as a good general combiner for, days to 50% flowering, days to 50% siliqua formation, linolenic acid (%), number of secondary branches, siliquae per plant, and seeds per siliqua, while ZM-R-6 for 100-seed weight, protein, and oleic acid percentage. ZM-R-11 × ZM-R-2 was identified as a good specific combiner for days to flowering, 50% flowering, and 50% siliqua (-5.19**, -4.70**, -5.37**), while ZM-M-6 × ZM-R-2, ZN-M-9 × ZM-R-6, ZN-R-8 × ZM-R-6, Shiralee × ZM-R-2 were good specific combiners for seeds per siliqua, 100-seed weight, oil, and protein percentage, respectively. Highly significant and desired mid-parent heterosis was observed for ZM-R-7 × ZM-R-2 for different morphological and quality traits like linolenic acid content and Shiralee × ZM-R-2 for oil (24.87**) and protein content (19.27**). Positive mid parental heterosis for oleic acid (46.81**), linoleic acid, and seed yield plant-1 were observed in ZM-R-7 × ZM-R-10 and ZN-M-9 × ZM-R-10. These hybrids can be utilized as a source of genetic material for future breeding programs.